FREEZABILITY AND FERTILITY OF FROZEN-THAWED KABASHI ECO-TYPE DESERT RAMS SEMEN PROCESSED WITH TRIS-SOYBEAN AND TRIS-EGG YOLK BASED EXTENDERS (Journal of Veterinary Medicine and Animal Production, 2022)
The present study was desinged to examine the effect of season and type of extender on the freezability and fertility of Kabbashi ram semen. Freezability was assessed by comparing the motility and viability of the frozen-thawed semenprocessed with a commercial soybean-based semen extender (AndroMed) with home-made Tris-based glucose/egg yolk extender. Fertility of the frozen-thawed semen processed with the two extenders was measured by the non-return rate to oestrus (NRR) after cervical insemination of ewes (n=60) treated with an intravaginal sponge containing 40 mg fluoroprogesterone acetate (FGA) for 12 days and an im injection of 500 IU eCG at the time of FGA sponge removal. Insemination was carried out 56 hours after removal of the FGA sponge. Season had no significant effect on post-thawing motility. Significant interaction between the effects of season and the type of extender on the post-thaw motility was observed (P < 0.001). The highest post-thawing motility for AndroMed was recorded in autumn while that for the home-made extender was in winter. The lowest value was observed in summer for the home-made extender . The NRR were not significantly different among semen samples processed with AndroMed (67.9%), and the Tris (74.1%) extenders. The overall conception and lambing rates were 71 and 25%, respectively. The prolificacy rates from ewes inseminated with frozen-thawed semen processed with AndroMed and the Tris(1.14, and 1.0, respectively) were also not significantly different. The present results indicated no significant seasonal effect on post-thawing motility. Significant interaction between season and type of extender was observed with consistent performance for AndroMed in all seasons. Thus, an egg yolkcontaining semen extender can be replaced with the lecithin-based extender(AndroMed), which could be used for cervical insemination using frozen-thawed ram semen without reducing its fertility